2018
DOI: 10.1111/head.13327
|View full text |Cite
|
Sign up to set email alerts
|

Use of Most Bothersome Symptom as a Coprimary Endpoint in Migraine Clinical Trials: A Post‐Hoc Analysis of the Pivotal ZOTRIP Randomized, Controlled Trial

Abstract: ObjectiveTo better understand the utility of using pain freedom and most bothersome headache‐associated symptom (MBS) freedom as co‐primary endpoints in clinical trials of acute migraine interventions.BackgroundAdhesive dermally applied microarray (ADAM) is an investigational system for intracutaneous drug administration. The recently completed pivotal Phase 2b/3 study (ZOTRIP), evaluating ADAM zolmitriptan for the treatment of acute moderate to severe migraine, was one of the first large studies to incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Initial models included all covariates, but the following variables were eliminated from the final model estimates because they did not significantly contribute to predicting the presence of the selected MBS: MIDAS, MHD frequency, medication overuse, MSSS, PROMIS Pain Interference, TPI, PHQ-2 anxiety, and PHQ-2 depression. b Monthly headache days over the past 90 days, divided by 3. c Responses to 12 ASC questions scored as 0 (never or rarely), 1 (less than half the time), and 2 (half the time or more), and summed (range 0-24), categories: none (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9 or more). The nausea MBS model found that men were less likely than women to designate nausea as their MBS (OR .77, 95% CI .66, .89).…”
Section: Resultsmentioning
confidence: 99%
“…Initial models included all covariates, but the following variables were eliminated from the final model estimates because they did not significantly contribute to predicting the presence of the selected MBS: MIDAS, MHD frequency, medication overuse, MSSS, PROMIS Pain Interference, TPI, PHQ-2 anxiety, and PHQ-2 depression. b Monthly headache days over the past 90 days, divided by 3. c Responses to 12 ASC questions scored as 0 (never or rarely), 1 (less than half the time), and 2 (half the time or more), and summed (range 0-24), categories: none (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9 or more). The nausea MBS model found that men were less likely than women to designate nausea as their MBS (OR .77, 95% CI .66, .89).…”
Section: Resultsmentioning
confidence: 99%
“…Trials differed in size and design, with several trials investigating multiple drug doses. Notably, in trials investigating ubrogepant and sumatriptan injection, MBS was identified at the time of treatment, whereas in the trial investigating ADAM zolmitriptan, patients prespecified their usual MBS on the first day of the run‐in period and were required to have that symptom at the time of the treated migraine . For the remaining trials, insufficient information has been published thus far to ascertain when MBS was specified.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation between 2‐hour MBS freedom and 2‐hour pain freedom is unknown and may be inconstant. Notably however, in the recently completed ZOTRIP trial, only 1 patient (<1%) achieved pain freedom without achieving MBS freedom …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations